2010
DOI: 10.1186/1471-2458-10-758
|View full text |Cite
|
Sign up to set email alerts
|

Do socioeconomic differences in tobacco use exist also in developing countries? A study of Ghanaian adolescents

Abstract: BackgroundIn Western countries, tobacco use is most prevalent among adolescents in lower socioeconomic groups. The association between socioeconomic status (SES) and tobacco use among adolescents in developing countries is unexplored. Using multiple SES measures, we investigated this association among adolescents in Ghana.MethodA school-based survey of a representative sample of 13-18-year-old Ghanaians (N = 1,165, response rate = 89.7%) was conducted in three regions, in 2008. Logistic regression analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 23 publications
6
34
1
Order By: Relevance
“…Our finding that intergenerational social mobility relates to smoking behaviour is also confirmed by the literature [15,26,35,38,39,40,41,42,43]. Lower smoking rates among young people with a stable high SES and those who experienced social upward mobility, and a higher inclination towards smoking in peers with a stable low SES and those who experienced social downward mobility, have been reported in studies from Scotland [15], France [38] and Ghana [40], among others. Already published KiGGS data have shown that intergenerational educational mobility also affects adolescents’ risk of obesity [50], multiple health behaviours [53,54], behavioural problems and their use of violence [55].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that intergenerational social mobility relates to smoking behaviour is also confirmed by the literature [15,26,35,38,39,40,41,42,43]. Lower smoking rates among young people with a stable high SES and those who experienced social upward mobility, and a higher inclination towards smoking in peers with a stable low SES and those who experienced social downward mobility, have been reported in studies from Scotland [15], France [38] and Ghana [40], among others. Already published KiGGS data have shown that intergenerational educational mobility also affects adolescents’ risk of obesity [50], multiple health behaviours [53,54], behavioural problems and their use of violence [55].…”
Section: Discussionsupporting
confidence: 91%
“…Other studies that directly compared the impact of various SES measures consistently report that indicators of adolescent SES are more relevant for adolescent smoking behaviour than parental SES indicators [15,24,25,26,28,29,31]. Our finding that intergenerational social mobility relates to smoking behaviour is also confirmed by the literature [15,26,35,38,39,40,41,42,43]. Lower smoking rates among young people with a stable high SES and those who experienced social upward mobility, and a higher inclination towards smoking in peers with a stable low SES and those who experienced social downward mobility, have been reported in studies from Scotland [15], France [38] and Ghana [40], among others.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However , less is known about the strength of this relationship among adolescents. Although an inverse relationship between parent ' s SES and prevalence of smoking by adolescents has been reported in developed countries ( Blow, Leicester, & Windmeijer, 2005 ;Borland, 1975 ;Soteriades & DiFranza, 2003 ), we have found only one study of the association of SES with tobacco use in adolescents from developing nations ( Doku, Koivusilta, Raisamo, & Rimpela, 2010 ).…”
Section: Ses and Tobacco Consumption Among Adolescentsmentioning
confidence: 60%
“…This is the fi rst study showing an association between tobacco consumption among youth and poverty in Latin America. Other studies have explored the relationship between tobacco and poverty, mainly in developed countries ( Blow et al, 2005 ;Borland, 1975 ;Doku et al, 2010 ;Harrell, Bangdiwala, Deng, Webb, & Bradley, 1998 ;Lowry, Kann, Collins, & Kolbe, 1996 ;Soteriades & DiFranza, 2003 ;Zhu, Liu, Shelton, Liu, & Giovino, 1996 ).This study has several limitations. First, an important limitation is that the GYTS does not include questions about individual-level SES , which prevented the investigation of individual-level SES as a confounder or effect modifi er.…”
Section: Declaration Of Interestsmentioning
confidence: 91%